Interventional Radiology-Guided Procedures in the Treatment of Pediatric Solid Tumors: A Systematic Review and Meta-Analysis - Zambaiti, Elisa; Siles Hinojosa, Alexander; Montano, Valentina; Mutanen, Annika; Glenisson, Mathilde; Sarnacki, Sabine; Franchi Abella, Stephanie; Pariente, Daniele; Pio, Luca (European Journal of Pediatric Surgery, 2020)
Introduction The use of interventional radiology (IR) in the treatment of pediatric solid tumors has markedly increased over the last three decades. However, data on effectiveness of IR-techniques, such as embolization/ablation, are scarce. In this systematic review and meta-analysis, we examined the outcomes of IR-procedures in the treatment of solid tumors in children.Materials and Methods Using a defined search strategy, we searched for studies reporting the use of IR-techniques for pediatric solid tumors from 1980 to 2017. Reports with less than three patients, review, and opinion articles were excluded. The study was conducted under preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. We analyzed dichotomous and continuous variables by appropriate statistical methods.Results Of 567 articles screened, 21 papers met the inclusion criteria (12 retrospective, 7 prospective, and 2 randomized-control trials). Many of the analyzed papers described relatively small cohorts of patients. IR-guided procedures were mainly rescue procedures to treat primarily unresectable tumors, local recurrences, or metastases. Inclusion/exclusion criteria and success definition were not specified in most reports. Major side effects were documented in 17/286 (6%) infants, while minor side effects were self-limiting in most patients. Six studies had a comparison between tumor embolization (127 infants) to surgery or chemotherapy without IR-procedures (113 controls). The meta-analysis showed lower mortality (16 vs. 47%) and surgical time for resection (206 vs. 250 m), higher 2-year tumor-free survival (82 vs. 36%), and favorable histology in IR group (p < 0.001 for all).Conclusion IR-guided techniques are promising in the treatment of pediatric solid tumors. Further prospective (randomized) trials are needed to clarify efficacy.
Keywords: interventional radiology; pediatric surgical oncology; radiologic embolization; pediatric oncology